2019
DOI: 10.1002/jcb.28904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrantly methylated differentially expressed genes in breast cancer by integrated bioinformatics analysis

Abstract: Background Abnormal DNA methylation has been demonstrated to drive breast cancer tumorigenesis. Thus, this study aimed to explore differentially expressed biomarkers driven by aberrant methylation in breast cancer and explore potential pathological mechanisms using comprehensive bioinformatics analysis. Methods Gene microarray datasets of expression (GSE45827) and methylation (GSE32393) were extracted from the Gene Expression Omnibus database. Abnormally methylated differentially expressed genes (DEGs) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…There are evidences that indicate identification of valuable biomarkers using transcriptomics 11 13 . Although some studies have revealed aberrant DNA methylation in GBM, limited research has been conducted on the comprehensive analysis of gene expression, methylation, and underlying molecular mechanisms 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…There are evidences that indicate identification of valuable biomarkers using transcriptomics 11 13 . Although some studies have revealed aberrant DNA methylation in GBM, limited research has been conducted on the comprehensive analysis of gene expression, methylation, and underlying molecular mechanisms 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…And Cai [ 10 ] use different data set to find the new hub gene CDCA5, which can change the cell cycle and make cells proliferate. In addition, many MDEGs are discussed in other systems, such as breast cancer, [ 11 ] osteosarcoma, [ 12 ] nasopharyngeal carcinoma, [ 13 ] and ovarian cancer. [ 14 ] Because the early symptoms are not obvious, most CCA patients have been diagnosed at the terminal stage.…”
Section: Discussionmentioning
confidence: 99%
“…23 DNA methylation biomarkers can be used as prognostic markers for the treatment of human cancers. 24 Therefore, exploring potential DNA methylation biomarkers is very important and urgently needed. In this study, differentially methylated CpG sites between breast cancer tissues and adjacent tissues were selected.…”
Section: Discussionmentioning
confidence: 99%